Melanin-like polydopa amides – synthesis and application in functionalization of magnetic nanoparticles1. Issue 11 (21st March 2015) - Petran, Anca; Mrówczyński, Radosław; Filip, Claudiu; Turcu, Rodica; Liebscher, Jürgen
<x xml:space="preserve">Abstract</x> Polydopa amides as new polymers synthesized by oxidative polymerization of dopa amides are used as coatings for magnetite nanoparticles.